PERANCANGAN KINCIR AIR PEMBANGKIT LISTRIK TENAGA MIKROHIDRO ALIRAN HEAD RENDAH: Studi Kasus Di Desa Manemeng Kecamatan Brang Ene Kabupaten Sumbawa Barat - Haizan; Mietra Anggara; Fadhli Dzhil Ikram; Aldrin (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
This study designs a water wheel for micro-hydropower generation with low-head flow of the Undershot type. The water wheel is designed with a head height of 0.5 meters, a diameter of 1.10 meters, and 16 blades, producing a planned power of 6.536 kW. The peripheral speed of the wheel is 0.28 meters per second with a rotation speed of 4.05 rpm. The blade receives water at a rate of 1.4 m³/second, generating a fluid force of 840 Newtons. The angular velocity of the wheel is 0.424 rad/second, and the shaft power is 5.556 kW with a shaft diameter of 0.10 meters. The static equivalent load is calculated to be 438.91 Newtons. This water wheel is expected to utilize slow but constant water flow to generate electricity, helping the rice field area in Manemeng village to maximize harvest yields and control pests.